Analysis on some Factors Influencing Employees Motivation and its Implication on Employees Performance in Packaging Company in Tangerang - Sukmayuda, Dede Nuary; Moeins, Anoesyirwan; Cahyono, Yoyok (International Review of Management and Marketing, 2019)
The main objective of this research is to study and analyze some factors which influenced employees' motivation and its implication on employees' performance at packaging company in Tangerang. Analysis was carried out using the Descriptive Statistic Method and Inferential to look at the influence of exogenous variables to endogenous ones simultaneously and partially. Structural Equation Model (SEM) was used with sub-structured composition as follows: Leadership, Organization Culture and Career Planning as exogenous variable and Motivation as endogenous variable (Y). The main structure this research consists of: Leadership, Organization Culture, Career Planning and Motivation as Exogenous variables and Employees' Performance as endogenous variables (Z). Research was carried out for 12 months using 398 respondents from 3100 employees at four packaging companies in Tangerang. Questionnaires were also distributed before research was done. Based on the research findings all independent variables have a significant effect on dependent variables partially or simultaneously. Together, leadership, organizational culture and career planning have an effect to motivation with R2 = 0.89 which means 89% with leadership as the most influential factor. It follows that leadership, organizational culture, career planning and motivation together have an effect to employees' performance with R 2 = 0.92 with organizational culture as the most influential factor. Results have also shown that 8% of other variables have some influences on employees' performance. Keywords: Leadership, Organizational Culture, Career Planning, Motivation, Employees Performance. JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7461